Empati Dan Penerimaan Sosial Siswa Reguler Terhadap Siswa ABK - Sandra, Okta Novrika; Zuhroh, Lutfiatuz (Psikodinamika: Jurnal Literasi Psikologi, 2021)
There are many cases of refusal of regular students to students with special needs due to their differences and limitations. Regular students have not been able to understand the situation of ABK students with all their limitations, they see ABK students with their eyes as normal students, without trying to imagine what if they are in the position of ABK students. This study aims to determine the relationship between empathy and self-acceptance of regular students towards students with special needs in the inclusive class at SD Inclusive Ulil Albab Kepanjen. This study uses quantitative methods using the product moment correlation data analysis technique. The research sample consisted of 53 regular students, where the subject was a regular student who happened to be met and was suitable as a data source. There are two measuring instruments used are (1) the scale of empathy and (2) the scale of social acceptance. From the results of the study and discussion, it is concluded that this research hypothesis is accepted. This indicates that empathy is positively correlated with social acceptance. So that the higher the level of empathy, the higher the level of social acceptance of regular students to ABK students in the inclusive class at Ulil Albab Inclusive Elementary School.